The safety of health care for ethnic minority patients: a systematic review - Chauhan, Ashfaq; Walton, Merrilyn; Manias, Elizabeth; Walpola, Ramesh Lahiru; Seale, Holly; Latanik, Monika; Leone, Desiree; Mears, Stephen; Harrison, Reema (International journal for equity in health, 2020)
Evidence to date indicates that patients from ethnic minority backgrounds may experience disparity in the quality and safety of health care they receive due to a range of socio-cultural factors. Although heightened risk of patient safety events is of key concern, there is a dearth of evidence regarding the nature and rate of patient safety events occurring amongst ethnic minority consumers, which is critical for the development of relevant intervention approaches to enhance the safety of their care. To establish how ethnic minority populations are conceptualised in the international literature, and the implications of this in shaping of our findings; the evidence of patient safety events arising among ethnic minority healthcare consumers internationally; and the individual, service and system factors that contribute to unsafe care. A systematic review of five databases (MEDLINE, PUBMED, PsycINFO, EMBASE and CINAHL) were undertaken using subject headings (MeSH) and keywords to identify studies relevant to our objectives. Inclusion criteria were applied independently by two researchers. A narrative synthesis was undertaken due to heterogeneity of the study designs of included studies followed by a study appraisal process. Forty-five studies were included in this review. Findings indicate that: (1) those from ethnic minority backgrounds were conceptualised variably; (2) people from ethnic minority backgrounds had higher rates of hospital acquired infections, complications, adverse drug events and dosing errors when compared to the wider population; and (3) factors including language proficiency, beliefs about illness and treatment, formal and informal interpreter use, consumer engagement, and interactions with health professionals contributed to increased risk of safety events amongst these populations. Ethnic minority consumers may experience inequity in the safety of care and be at higher risk of patient safety events. Health services and systems must consider the individual, inter- and intra-ethnic variations in the nature of safety events to understand the where and how to invest resource to enhance equity in the safety of care. This systematic review is registered with Research Registry: reviewregistry761.